O bom filho a casa sempre torna: análise do relacionamento entre a Universidade Federal de Minas Gerais e seus egressos por meio da informação - Tatiana Pereira Queiroz (2014)
Keeping contact with the student after his/her graduation is not an usual habit found in most of current Brazilian Higher Education institutions.This connection, fundamental to the consolidation and continuation of these institutions, is conceived during the course of study, and the promotion of positive experiences is important to the construction of these bonds. Information, in this case, seems to stand out as it is through it that contact will be kept with alumni. On the other hand, the system implies the materialization of these pieces of information. When it centralizes them, in order to cater to both graduates and the management board of the institution, it facilitates the continuity of this relationship. Based on this context, we were interested in investigating how the relationship between former students and their university happens in this case, UFMG, represented by its former student program: Sempre UFMG. Through an electronic survey, 1445 undergraduation and graduation ex-students from the aforementioned institution answered questions that covered three categories of analysis: demographic/academic profile, identification/linking profile and the Sempre UFMG information user profile. After data description, making associations among some variables of interest, using Pearsons qui square test and UFMGs development assessment index, using exploratory factor analysis, we observed a high tendency of former students to maintain the connection with the university.That happened specially through the reception of information via email focusing on continuing studies, such as post-graduation and extension courses. The majority of interviewees had a positive evaluation of the institution and, even when it was not so scathing, it was still in agreement with the university. Some suggestions were given to improve Sempre UFMG information system and its services, in order to facilitate the bond maintenance between the institution and its former students.